THE EFFECT OF DEBATE TECHNIQUE ON THE SPEAKING ABILITY OF THE SECOND YEAR STUDENTS OF SMA N 5 TUALANG - Julianty, Putri Eka; Afrianto, Afrianto; Eliwarti, Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research is aimed to find out whether there was some significant effect of debate technique on the ability of the second-year students of SMAN 5 Tualang. In conducting the research, pre-experimental research with one group pre-test post-test design was used. The sample of this research was the students of class XI IPA IV consisting of 30 students. The pre-test was administered before the treatment. After the treatment was applied for five meetings using debate technique, a post-test was administered. The data were analyzed using t-test formula. From the result, the researcher found that the value of t-test was 15.690 while the t-table was 2.045. Since the t-test was higher than t-table, alternative hypothesis of this research is. It means that there is a significant effect of debate technique on the ability of the second- year students of SMAN 5 Tualang in speaking.Key Words: Speaking Ability, Debate Technique, Senior High School Students.